Estimating alcohol‐attributable liver disease mortality: A comparison of methods. (1st April 2022) - Sherk, Adam; Esser, Marissa B.; Stockwell, Tim; Naimi, Timothy S.
Abstract: Introduction: Alcohol is a leading contributor to liver disease, however, estimating the proportion of liver disease deaths attributable to alcohol use can be methodologically challenging. Methods: We compared three approaches for estimating alcohol‐attributable liver disease deaths (AALDD), using the USA as an example. One involved summing deaths from alcoholic liver disease and a proportion from unspecified cirrhosis (direct method); two used population attributable fraction (PAF) methodology, including one that adjusted for per capita alcohol sales. For PAFs, the 2011–2015 Behavioral Risk Factor Surveillance System and per capita sales from the Alcohol Epidemiologic Data System were used to derive alcohol consumption prevalence estimates at various levels (excessive alcohol use was defined by medium and high consumption levels). Prevalence estimates were used with relative risks from two meta‐analyses, and PAFs were applied to the 2011–2015 average annual number of deaths from alcoholic cirrhosis and unspecified cirrhosis (using National Vital Statistics System data) to estimate AALDD. Results: The number of AALDD was higher using the direct method (28 345 annually) than the PAF methods, but similar when alcohol prevalence was adjusted using per capita sales and all alcohol consumption levels were considered (e.g. 25 145 AALDD). Using the PAF method, disaggregating non‐drinkers into lifetime abstainers and former drinkers to incorporate relative risks for former drinkers yielded higher AALDD estimates (e.g. 27 686) than methods with all non‐drinkers combined. Discussion and Conclusions: Using PAF methods that adjust for per capita sales and model risks for former drinkers yield more complete and possibly more valid AALDD estimates.